An Autonomous Home Energy Management System Using Dynamic Priority Strategy in Conventional Homes - Shakeri M.; Amin N.; Pasupuleti J.; Mehbodniya A.; Asim N.; Tiong S.K.; Low F.W.; Yaw C.T.; Samsudin N.A.; Rokonuzzaman M.; Hen C.K.; Lai C.W. (MDPI AG, 2023)
Costs; Energy management; Energy utilization; Demand response programs; Electrical appliances; Energy management strategies; Home energy management systems; Peak to average ratios; Real time pricing; Smart technology; Utility companies; Energy management systems